Performance of private equity funds in emerging markets: an empirical analysis - Sleczka, Oliver (2017)
This paper investigates the performance of private equity funds in emerging markets based on data of individual fund level returns from 1995 to 2013 obtained from Preqin. The research focus of this thesis lies on performance drivers and return persistence. The analysis is divided in two parts. The first part investigates the relationship between fund performance and fund characteristics focusing on the GP location, the investment focus, as well as the fund size, sequence number, and GP experience. The key objective is to determine significant emerging market-specific performance factors. Our results suggest that funds with a clear geographic investment focus earn significantly higher returns. The second part aims to find evidence for persistence in the performance of emerging market private equity funds. The findings corroborate the hypothesis that unlike in developed markets, performance persistence still exists in emerging markets.